2014
DOI: 10.1103/physreve.90.043011
|View full text |Cite
|
Sign up to set email alerts
|

Filling of charged cylindrical capillaries

Abstract: We provide an analytical model to describe the filling dynamics of horizontal cylindrical capillaries having charged walls. The presence of surface charge leads to two distinct effects: It leads to a retarding electrical force on the liquid column and also causes a reduced viscous drag force because of decreased velocity gradients at the wall. Both these effects essentially stem from the spontaneous formation of an electric double layer (EDL) and the resulting streaming potential caused by the net capillary-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 93 publications
1
14
0
Order By: Relevance
“…In the presence of ion partitioning effects, the number density of the electrolyte ions obeys the modified Boltzmann equation, namely: where the bulk number concentration n 0 stands for the ionic number concentration of cations and anions in the bulk electrolyte reservoir (where ψ = 0) connecting the soft nanochannel, k b is the Boltzmann constant, and T av is the average temperature. It is worth nothing that Equations (5) and (6) remain valid for different EDL thicknesses, so the Boltzmann distribution is able to be used even though EDLs overlap [ 47 , 48 , 49 ]. The term ∆ W ± , the Born energy difference, identifies the ion partitioning effect, which is related to different permittivities for the two layers.…”
Section: Mathematical Model Analysismentioning
confidence: 99%
“…In the presence of ion partitioning effects, the number density of the electrolyte ions obeys the modified Boltzmann equation, namely: where the bulk number concentration n 0 stands for the ionic number concentration of cations and anions in the bulk electrolyte reservoir (where ψ = 0) connecting the soft nanochannel, k b is the Boltzmann constant, and T av is the average temperature. It is worth nothing that Equations (5) and (6) remain valid for different EDL thicknesses, so the Boltzmann distribution is able to be used even though EDLs overlap [ 47 , 48 , 49 ]. The term ∆ W ± , the Born energy difference, identifies the ion partitioning effect, which is related to different permittivities for the two layers.…”
Section: Mathematical Model Analysismentioning
confidence: 99%
“…Due to the generation of EDL at the walls of these capillaries, ζpotential of ψ0 is developed. To obtain potential distribution (ψ) across such a single channel, one can employ the Poisson-Boltzmann equation 47 :…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Since the medium has an extremely low conductivity, the presence of any electrical double layer (EDL) 38,39 and its effect on the capillary dynamics may be safely ruled out. Nevertheless, studies have been reported in the literature where the influence of the association of EDLs with the capillary transport has been looked into, 40 albeit for Newtonian fluids.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…To this end, we apply a reduced order approach to determine the dynamic evolution of the fluid height as function of electric field and particle concentration. Nevertheless, studies have been reported in the literature where influence of the association of EDL with the capillary transport has been looked into 40 , albeit for Newtonian fluids. We consider the classical Bingham model for the ERFs, which finds diverse use for modeling of electrorheological flows 1,37 and successfully matches with experimental findings.…”
Section: Introductionmentioning
confidence: 99%